Metal uptake and distribution in the zebrafish (Danio rerio) embryo: differences between nanoparticles and metal ions. Issue 5 (17th March 2017) - Böhme, Steffi; Baccaro, Marta; Schmidt, Matthias; Potthoff, Annegret; Stärk, Hans-Joachim; Reemtsma, Thorsten; Kühnel, Dana
Abstract : Quantitative data on nanoparticle and cation uptake are compared in a compartment-specific way and distinct differences between metals were identified. Abstract : The zebrafish ( Danio rerio ) embryo (ZFE) is an established test organism for investigating the toxicity of chemicals and is suitable for the assessment of the hazardous potential of nanoparticles. There is little knowledge on metal internalization and distribution in these organisms, as well as on the underlying kinetic processes. To shed light on metal–ZFE interactions, the uptake of different metal-composed nanoparticles (Ag-, Au-, CuO-, ZnO-NP) and their dissolved cations was studied in terms of temporal and spatial distribution as well as internal concentrations considering different ZFE compartments (whole egg, embryo, chorion, perivitelline space). By applying laser ablation ICP-MS and electron microscopy, element-specific differences in metal distribution at the surface and within the test organisms were observed. As determined by nebulization ICP-MS, all metals showed a bioconcentration in the eggs. Gold showed the highest accumulation, followed by silver, zinc and copper, with distinct differences when comparing the uptake of nanoparticles and metal ions. Upon exposure to nanoparticles, more silver and zinc were detected in the organisms, whereas more copper accumulated upon exposure to the cations. For silver, gold, and copper, the major share was found at the chorion structures, irrespective of exposure to NPs or cations. In contrast, for zinc, the highest portion reached the inner embryo. Overall, our results provide an informative basis to explain the differences in nanoparticle and ion toxicity observed in various studies.